Maternal vitamin D status during pregnancy and infant’s gut microbiota: a prospective cohort study - Song, Qiying; Li, Yao; Zhou, Tao; Xiao, Meiqun; Xiao, Bin; Wang, Mengying; Zhu, Yuanfang (Frontiers in Nutrition, 2024)
Objectives: To prospectively explore the association of maternal serum 25(OH)D levels with the infant's gut microbiota in Chinese populations, and to evaluate its potential influence on the dynamic change patterns of offspring's gut microbiota from 1 to 6 months old.Methods: Eighty-seven mother-infant dyads (vitamin D insufficient group v.s. normal group = 59 v.s. 28) were included in this longitudinal study. Two fecal samples were collected for the included infant at home by the parents at 1 month of age ("M1 phase") and 6 months of age ("M6 phase"). Gut microbiota were profiled by 16S rRNA gene sequencing. We performed mixed effects models on alpha diversity metrics, PERMANOVA tests on beta diversity distances, and linear discriminant analysis (LDA) to identify differently abundant taxa.We observed significantly lower Pielou's evenness and Shannon diversity in the vitamin D insufficient group in the M6 phase (P = 0.049 and 0.015, respectively), but not in the M1 phase (P>0.05), and the dynamic changes in alpha diversity from 1 to 6 months old were significantly different according to maternal vitamin D status (P<0.05). There were also significant differences in gut microbiota composition between the vitamin D insufficient group and normal group, both in the M1 and M6 phases (LDA score>2.0, P<0.05). Moreover, among the predicted metagenome functions, pathways related to amino acid biosynthesis, starch degradation, and purine nucleotides biosynthesis were enriched in the vitamin D insufficient group.Our findings highlight that maternal vitamin D status plays a pivotal role in shaping the early-life gut microbiota of the next generation.